Multicritical behaviour in magnetic ﬂuids - Schinagl, F.; Folk, R.; Iro, H. (Condensed Matter Physics, 1999)
The phases of a magnetic fluid in an external field are considered. As
model systems we take an ideal (hard core) gas with Ising interaction and
a van der Waals gas with additional Heisenberg interaction. In mean field
approximation various phases and critical points are identified. For appropriate
values of the ratio of the magnetic to the non-magnetic interactions
there exist multicritical points like tricritical points and critical end points.
For the ideal Ising fluid we calculate the line of wing critical points analytically
and prove classical tricritical behaviour. In the van der Waals case
wing critical points and the gas-liquid critical point may coexist. The corresponding
phase diagrams in (p, t, h)-space are shown. Для моделей ідеального (тверді кульки) газу із взаємодією Ізінга та
газу Ван дер Ваальса із взаємодією типу Гайзенберга досліджуються фази магнітного флюїду у зовнішньому полі. У наближенні середнього поля ідентифіковані різні фази та критичні точки. Показано,
що для певних значень відношення констант магнітної та немагнітної взаємодій існують мультикритичні точки типу трикритичних і критичних кінцевих точок. Для моделі ідеального ізінгівського флюїду
аналітично розраховано бокові лінії критичних точок та знайдено класичну трикритичну поведінку. У випадку моделі Ван дер Ваальса бокові критичні лінії та критична точка можуть співіснувати. Наведені
відповідні фазові діаграми у змінних (p, t, h).